COST AND RETURNS STRUCTURE OF GARRI PROCESSING AMONG COOPERATIVE WOMEN IN IJEBU-DIVISION OF OGUN-STATE, NIGERIA - Adesina, Shittu K.; Adebayo, Omowunmi Mercy; Jimoh, Bashiru Oladayo (FUDMA JOURNAL OF SCIENCES, 2025)
The study examined cost and returns structure of Garri processing among cooperative women Ijebu-Division of Ogun State, Nigeria. A two-stage sampling technique was used to select sample size of 120 respondents using structured questionnaire to generate required information from respondents. Data analysis was carried out using descriptive and inferential statistics.The result revealed that majority (98.3%) of the respondents had formal education. Garri processors had much years experience in their business with a mean of households’ size of 5 persons. Majority (82.5%) of Garri processors were married with an average age of 38 years old. The budgetary analysis result revealed that garri processing was found to be highly profitable at net income of N14,167.74 and gross margin N27,298.35 per annum. Likewise, benefit-cost B/C of 1.46 also revealed that for every one naira spent on Garri processing there was a return of N0:46k, this showed that Garri processing is a highly viable and profitable business. Bad road, lack of capital, poor and instable price of garri, high cost of transportation were major constraints militating against garri processing. Therefore, the study recommended that, problems confronting Garri processors should be addressed properly. Government should help garri processors by providing agricultural loans with no or low interest rates with comfortable loan repayment period. People who are jobless can also engage themselves in Garri processing to create job for themselves. Garri producers should form themselves into cooperative groups and pool their resources together for easy access of Garri processing inputs.